(untitled) (CIPEEX, 2025)
The relationship between Chronic Obstructive Pulmonary Disease (COPD) and muscle mass loss, or sarcopenia, highlights the relevance of nutritional interventions, such as protein supplementation, in the management of the disease. COPD is characterized by chronic airflow obstruction and is associated with systemic manifestations, such as muscular and cardiovascular changes. The prevalence of COPD in Brazil ranges from 6% to 15.8% of the population over 40 years old, representing millions of affected individuals. The treatment of COPD involves a multidisciplinary approach, with the use of medications and interventions such as pulmonary rehabilitation and nutritional support, where adequate protein intake is essential for patients with severe COPD. Protein supplementation, combined with physical exercise, has shown benefits in preserving muscle mass and improving the quality of life for these patients. The proposed study aims to evaluate the relationship between nutritional status and sarcopenia in patients with severe COPD, as well as investigate the effects of supplementation with collagen hydrolysate peptides on improving muscle conditions. Volunteers will be recruited through advertisements, and participants will be divided into two groups: one will undergo evaluation only, and the other will receive collagen supplementation. The study will use anthropometric measurements, bioimpedance, and muscle strength tests to assess the results. The data will be analyzed using statistical software, and the study is expected to demonstrate the efficacy of protein supplementation, potentially opening a new market for collagen hydrolysate in the treatment of patients with severe COPD.